Analysis of the Effect of Earnings per share, Price earning ratio and Price to book value on the stock prices of state-owned enterprises - Sari, Ratna (Golden Ratio of Finance Management, 2021)
This study aims to (1) determine the effect of earnings per share on stock prices, (2) determine the effect of price-earnings ratio on stock prices, (3 determine the effect of price to book value on stock prices, (4) find out whether earnings per share, price earning ratio, and price to book value have a simultaneous effect on stock prices. This study uses secondary data through data sources and the Indonesian stock exchange that have been published by companies, as many as nine companies within five years. This research was conducted within the research period. From August to October 2020. Methods: the analysis used is multiple linear regression analysis, classical assumption test, partial test, simultaneous test, and coefficient of determination. The data were analyzed using the Statistical Product and Service Solution (SPSS) 23 software program. The results of this study state that (1) Earning Per Share has a positive and significant effect on stock prices, (2) price earning ratio has a positive and significant effect on stock prices, (3) price to book value has a positive and significant effect on stock prices, (4) Earning Per Share, price earning ratio, debt to equity, price to book value simultaneously affects the stock price. Therefore, construction companies are expected to improve their performance to increase stock prices further.